The autonomy of the commercial companies code — between unity and duality of private law - Kułak, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This study concerns the unity of private law and the idea of returning to its dualistic concept. The article’s reasoning is based on the perspective of the Commercial Companies Code which, despite the normatively sanctioned monistic approach, can be considered as a specific regulation due to afar-reaching autonomy to traditional civil law as well as encouragement to discuss the return to adual regulation of private law. Moreover, the current form of the provisions dedicated to commercial relations in the Civil code justifies the conclusion that we already have a regulatory dualism and that the notion of “unity” can be reasonably mentioned in the context of codification unity only. This circumstance, together with the progressive specialisation of trade and favourable socio-economic conditions, are inclined to review, reorganise, and complete the normative, essential regulation of this sphere either in the Civil code or in a new commercial code.
Keywords: commercial law; civil law; private law; company law; monism of private law; duality of private law; unity of private law; Commercial Companies Code; civil code; autonomy of company law